2015
DOI: 10.1016/j.concog.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory spillover effect: Controlling the bladder makes better liars

Abstract: The Inhibitory-Spillover-Effect (ISE) on a deception task was investigated. The ISE occurs when performance in one self-control task facilitates performance in another (simultaneously conducted) self-control task. Deceiving requires increased access to inhibitory control. We hypothesized that inducing liars to control urination urgency (physical inhibition) would facilitate control during deceptive interviews (cognitive inhibition). Participants drank small (low-control) or large (high-control) amounts of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Cognitive psychologists have reasoned that lying requires access to executive control processes involved in suppressing the truth, searching for information in long term memory, and assembling a lie in working memory (see Gombos, 2006; Walczyk et al, 2013, 2014; Sporer, 2016). Supporting these notions, neuroimaging studies have shown that brain areas involved in working memory, response monitoring and conflict, inhibition, and multitasking are active during deception (see meta-analyses by Christ et al, 2009; Farah et al, 2014; Gamer, 2014; Lisofsky et al, 2014), and cognitive psychology studies have shown that lying requires greater access to executive control processes than truth telling (e.g., Debey et al, 2012; Visu-Petra et al, 2013; Fenn et al, 2015). Finally, some linguistic markers of cognitive load are present more often in deceptive than in truthful accounts (Hauch et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Cognitive psychologists have reasoned that lying requires access to executive control processes involved in suppressing the truth, searching for information in long term memory, and assembling a lie in working memory (see Gombos, 2006; Walczyk et al, 2013, 2014; Sporer, 2016). Supporting these notions, neuroimaging studies have shown that brain areas involved in working memory, response monitoring and conflict, inhibition, and multitasking are active during deception (see meta-analyses by Christ et al, 2009; Farah et al, 2014; Gamer, 2014; Lisofsky et al, 2014), and cognitive psychology studies have shown that lying requires greater access to executive control processes than truth telling (e.g., Debey et al, 2012; Visu-Petra et al, 2013; Fenn et al, 2015). Finally, some linguistic markers of cognitive load are present more often in deceptive than in truthful accounts (Hauch et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…The idea of a common inhibitory network strengthened the assumption of the current study that changing the load of an inhibitory domain (physiological) will also change the load of another domain (resistance to distractor interference). However, studies on ISE using the same bladder pressure manipulation to create a concurrent inhibitory activation revealed that the diffusion of the inhibitory effects usually manifests itself by facilitation or an improvement in simultaneously occurring inhibitory-related task performances regardless of the type of inhibition (e.g., Fenn et al, 2015; Tuk et al, 2011). Considering this, the distractor interference may have been expected to be less for participants with high bladder pressure in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…When the participants completed the tests, bladder pressure manipulation was implemented. As in the Fenn et al (2015) study, an attempt was made to keep the participants’ attention away from their bladders as much as possible while maintaining the attention task, and to ensure that each participant performs the same actions during the waiting period for bladder pressure to occur. Thus, it was said that the effect of physiological factors on the decision-making processes will be measured by a group of questions about the water they drink.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory control refers to one's ability to restrain and override impulses to achieve goals of higher importance or with better payoffs . A growing body of literature highlights the existence of a common, domain‐independent capacity for inhibitory control . Specifically, when inhibitory control is activated in one domain, it can facilitate control in other (unrelated) domains.…”
Section: Introductionmentioning
confidence: 99%